Ferritin levels on hospital admission predict hypoxic-ischemic encephalopathy in patients after out-of-hospital cardiac arrest: a prospective observational single-center study - Nickelsen, Swantje; Grosse Darrelmann, Eleonore; Seidlmayer, Lea; Fink, Katrin; Britsch, Simone; Dürschmied, Daniel; Scharf, Rüdiger Eberhard; Elsässer, Albrecht; Helbing, Thomas (Journal of intensive care medicine, 2024)
Aim - Out-of-hospital cardiac arrest (OHCA) is a major health concern in Western societies. Poor outcome after OHCA is determined by the extent of hypoxic-ischemic encephalopathy (HIE). Dysregulation of iron metabolism has prognostic relevance in patients with ischemic stroke and sepsis. The aim of this study was to determine whether serum iron parameters help to estimate outcomes after OHCA. - Methods - In this prospective single-center study, 70 adult OHCA patients were analyzed. Serum ferritin, iron, transferrin (TRF), and TRF saturation (TRFS) were measured in blood samples drawn on day 0 (admission), day 2, day 4, and 6 months after the return of spontaneous circulation (ROSC). The association of 4 iron parameters with in-hospital mortality, neurological outcome (cerebral performance category [CPC]), and HIE was investigated by receiver operating characteristics and multivariate regression analyses. - Results - OHCA subjects displayed significantly increased serum ferritin levels on day 0 and lowered iron, TRF, and TRFS on days 2 and 4 after ROSC, as compared to concentrations measured at a 6-month follow-up. Iron parameters were not associated with in-hospital mortality or neurological outcomes according to the CPC. Ferritin on admission was an independent predictor of features of HIE on cranial computed tomography and death due to HIE. - Conclusion - OHCA is associated with alterations in iron metabolism that persist for several days after ROSC. Ferritin on admission can help to predict HIE.
Erstmals online veröffentlicht: 15. Mai 2024
Gesehen am 17.12.2024